2008
DOI: 10.1002/ar.20727
|View full text |Cite
|
Sign up to set email alerts
|

Newly Revealed Cricothyropharyngeus Muscle in the Human Laryngopharynx

Abstract: Humans have a uniquely curved pharynx and tongue that is believed to have evolved for speech. The most inferior part of the pharynx consists of the laryngopharynx, the critical crossroad where swallowing, breathing, and phonation overlap. We hypothesized that the human laryngopharynx has unique neuromuscular specializations that may be speech related. Laryngopharynx specimens from 15 humans and 20 nonhuman mammals (dog, pig, rabbit, and rat) were studied. Microdissection revealed that only human specimens had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In addition, distribution of the MEPs in each muscle is another indicator for delineating NMCs (Galvas and Gonyea, 1980; Mu and Sanders, 1998a,b, 2000b). Our studies have demonstrated that a number of upper airway muscles (Sanders et al, 1994; Mu and Sanders, 1998a,b, 1999, 2000b, 2001, 2007, 2008, 2009) including the tongue (present study) are composed of NMCs. The regional activation of the tongue muscles (Napadow et al, 1999) suggests that the NMCs within the tongue muscles are independently controlled to shape and regulate the various motions of the tongue.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In addition, distribution of the MEPs in each muscle is another indicator for delineating NMCs (Galvas and Gonyea, 1980; Mu and Sanders, 1998a,b, 2000b). Our studies have demonstrated that a number of upper airway muscles (Sanders et al, 1994; Mu and Sanders, 1998a,b, 1999, 2000b, 2001, 2007, 2008, 2009) including the tongue (present study) are composed of NMCs. The regional activation of the tongue muscles (Napadow et al, 1999) suggests that the NMCs within the tongue muscles are independently controlled to shape and regulate the various motions of the tongue.…”
Section: Discussionmentioning
confidence: 51%
“…The details regarding this technique have been given elsewhere (Mu and Sanders, 1999, 2008, 2009, 2010). Briefly, human tongue specimens were: 1) fixed for four weeks in 10% unneutralized formalin; 2) macerated for three weeks in 3% aqueous potassium hydroxide (KOH) solution (add 3 drops of 3% v/v hydrogen peroxide into 100 ml 3% w/v KOH solution for depigmentation) with several changes; 3) decalcified for two weeks in Sihler’s solution I (one volume glacial acetic acid, one volume glycerin, and six volumes 1% w/v aqueous chloral hydrate) with several changes; 4) stained for four weeks in Sihler’s solution II (one volume stock Ehrlich’s hematoxylin, one volume glycerin, and six volumes 1% w/v aqueous chloral hydrate); 5) destained for three hours in Sihler’s solution I; 6) immersed for one hour in 0.05% w/v lithium carbonate solution to darken the nerves; 7) cleared for three days in 50% v/v aqueous glycerin; and 8) preserved for 4 to 6 weeks in 100% glycerin with a few thymol crystals for transparency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu and Sanders (1992, 1994) were the first to apply the modified Sihler's staining technique to investigate the supply patterns of the laryngeal nerves. Using Sihler's stain, this group investigated extensively innervation of the larynx (Diamond et al 1992, Drake et al 1993, Sanders et al 1993a,b, 1994, Mu et al 1994, Wu et al 1994, Sanders and Mu 1998, Mu and Sanders 2009), pharynx (Mu and Sanders 1996, 1998a, 2000a, 2001, 2007, 2008), tongue (Mu and Sanders 1999, 2000b, Zur et al 2004), and other head and neck muscles (Mu and Sanders 1998b, Ren and Mu 2005) in humans and animals. Other researchers in this country also used Sihler's stain to investigate the nerve supply patterns of the skin (Hirigoyen et al 1996) and tongue (McClung and Goldberg 2000) in rats; temporalis (Ziccardi et al 1998), biceps brachii (Amirali et al 2007) muscles and tongue mucosa (Doty et al 2009) in humans, and laryngeal musculature in horses (Cheetham et al 2008).…”
Section: Applications Of Sihler's Stainmentioning
confidence: 99%
“…More recently, Mu and Sanders (2008) described a new muscle termed “cricothyropharyngeus” in the human laryngopharynx. The cricothyropharyngeus originates from the anterior arch of the cricoid cartilage, and courses between the inferior pharyngeal constrictor and cricopharyngeus muscles to insert into the median raphe at the posterior midline of the pharynx.…”
Section: Contributions Of Sihler's Stain To Neurosciencementioning
confidence: 99%